The Role of Controlled Breathing in Pain Management - Maria Wydro; Magdalena Grotowska; Martyna Łukasiewicz; Aleksandra Strawińska (Quality in Sport)
Breathing is a fundamental physiological process essential for cellular respiration and energy production. Beyond its physiological necessity, controlled breathing techniques such as yogic breathing etc. pranayama, have been practiced for centuries due to their perceived spiritual and health benefits, including stress reduction and pain management. Recent studies have explored the physiological effects of deep slow breathing (DSB), particularly its impact on the autonomic nervous system (ANS) and pain perception. Evidence suggests that breathing at a low frequency, such as 6 h per minute (bpm), enhances heart rate variability (HRV), promotes parasympathetic activity, and reduces stress and pain levels. This review examines the mechanisms underlying these effects, highlighting the role of the vagus nerve in regulating relaxation and reducing inflammation. Empirical studies demonstrate that DSB positively influences chronic pain conditions, including menstrual pain and visceral pain,  by modulating pain perception and emotional regulation. Additionally, the combination of DSB and vagus nerve stimulation (VNS) has shown promise in managing chronic pain and improving musculoskeletal pain thresholds. Despite promising findings in menstrual pain, visceral pain, and chronic conditions, further research is needed to elucidate the mechanisms and optimize breathing techniques for pain relief. However, while DSB and VNS have demonstrated potential in reducing pain and anxiety, current research is limited in scope and methodology. Further investigations are needed to establish their long-term benefits and optimize their use in pain management strategies. This review underscores the need for a deeper understanding of the connection between controlled breathing, vagal tone, and pain relief to support their clinical application.